NMR relaxometry analysis of molecular degradation in internal combustion engine lubricants. (26th October 2020) - Erro, Eustaquio M.; Gerbino, Leandro J.; Fraenza, Carla C.; Anoardo, Esteban
Abstract: A set of experimental techniques headed by proton fast field‐cycling nuclear magnetic resonance ( 1 HFFC‐NMR) were used to analyze the effects of degradation of lubricant oil used in an internal combustion engine (ICE). Its relaxometric, spectroscopic, and rheological properties were evaluated and interpreted in terms of changes in the chemical structure and the involved molecular dynamics. In order to better understand the relaxometric behavior, chemical changes induced by heat were investigated for selected n ‐alkanes, as model‐systems due to their structural simplicity. Fourier transform infrared (FTIR) spectroscopy, viscosity measurements, and foaming were used to contrast NMR relaxometry experiments. Main observed changes associated with oil degradation can be attributed to molecular oxidation, fragmentation, and ramification. As an outstanding feature of this work, we show that the relaxometric analysis can be done without any special treatment of the sample, allowing results in less than 10 min. Abstract : Proton fast field‐cycling NMR relaxometry was used to analyze degradation of an ICE lubricant. Observed changes can be attributed to molecular oxidation, fragmentation, and ramification. The relaxometric analysis can be done without any special treatment of the sample allowing results in less than 10 min.